Ensino de artes visuais e Políticas Públicas Educacionais - Rossi, Maria Helena Wagner; Magalhães, Ana Del Tabor Vasconcelos (Revista GEARTE, 2018)
Ensino de artes visuais e Políticas Públicas Educacionais